No way out - Newman, Alfred 1901-1970 (Twentieth Century Fox Home Entertainment LLC, 2018)
"Ein fanatisierter weißer Amerikaner schürt Rassenhaß und Gewalt, indem er nach dem Tod seines Bruders dessen schwarzen Arzt des Mordes bezichtigt. Der Film setzt sich ernsthaft und objektiv mit den amerikanischen Rassenproblemen auseinander. Formal stark auf äußere Spannung getrimmt [...] eine packende Veranschaulichung von (selbst-)zerstörerischer Gewalt und blindem Rassenhaß." [filmdienst.de]
Original: USA 1950
Bildformat 1.37:1 original aspect ratio
1080p presentation of the film on Blu-ray, with a progressive encode on the DVD ; LPCM mono soundtrack (Uncompressed on the Blu-ray) ; optional English subtitles for the deaf and hard-of-hearing ; Audio Commentary by film noir historian Eddie Muller ; All about Mankiewicz (103 minutes) - a massive two-part interview with the legendary director, featuring Michael Ciment and directed by Luc Béraud ; Archival Fox Movietone Newsreels ; original theatrical trailer ; a collector's booklet featuring a new essay by Glenn Kenny
Keywords: Film